Study guides

☆☆

Q: How do you solve 4x2 - 4x plus 2 equals 0?

Write your answer...

Submit

Related questions

4x2 = -12x, divide both sides by 4x: x = -3

4x2+50x = 0 4x(x+12.5) = 0 x = 0 or x = -12.5

4x2+49x+90 = (4x+9)(x+10) when factored

4x2 - 13 x + 3 = 0 (4x - 1)(x - 3) = 0 x = 3, 1/4

-((4x + 1)(x - 1))

4x2-4x+1 = (2x-1)(2x-1)

ANSWER: -4X2 -8X-4x (x+2)= (-4x * x) + (-4x*2)= -4X2 -8X

The answer is: x = -5/2 and x = 7/2

4x2=8 8+22=30 You get 30 it really is simple

(4x - 32)(x - 2) so x = 2 or 8

2y = 4x + 4y = 2x + 2

4x2-5x = 6 4x2-5x-6 = 0 (4x+3)(x-2) = 0 x = -3/4 or x = 2

many solutions

It is: -4x^2 +11x -6 equals (-4x+3)(x-2) when factored

x= -.5

-4x2 + 5x + 6 = 0 Multiply through by -1: 4x2 - 5x - 6 = 0 (I prefer the leading coefficient to be >0) 4x2 - 8x + 3x - 6 = 0 4x(x - 2) + 3(x - 2) = 0 (x - 2)(4x + 3) = 0 So x - 2 = 0 or 4x + 3 = 0 ie x = 2 or x = -3/4

4x2 - 4x + 2xy - 2y = 4x(x - 1) + 2y(x - 1) (4x + 2y)(x - 1).

You can't solve it. But you can simplify it to get: 4x+y=2

(4x+3)(x-5) = 0 x = -3/4 or x = 5

4x2+12x = 4x(x+3) when factored

Given, 4x2 - 4x + 3 = 0; then, 4x2 - 4x + 1 = (2x - 1)2 = -2, 2x - 1 = √-2 = ±i√2, and 2x = 1 ± i√2; therefore, x = ½(1 ± i√2).

It can be factored as: 4x(x+228)

(2,1)

8+4x

You cannot solve one linear equation with two variables.